1990
DOI: 10.1039/p19900002363
|View full text |Cite
|
Sign up to set email alerts
|

β-Amino acid isomers of a natural substrate of the enzyme γ-glutamyl-amino acid cyclotransferase. Synthesis of (3S)-3-aminoglutaryl-(S)-alanine and (3R)-3-aminoglutaryl-(S)-alanine

Abstract: The title compounds (VI) and (‐)‐(VIII) are potential inhibitors of the title enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…GA has been shown to have inhibitory activity (87 % at 1 m m ) when assessed using recombinant GGCT . Therefore, we evaluated the inhibitory effect of GA on GGCT activity in GGCT‐NIH‐3T3 cell homogenates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GA has been shown to have inhibitory activity (87 % at 1 m m ) when assessed using recombinant GGCT . Therefore, we evaluated the inhibitory effect of GA on GGCT activity in GGCT‐NIH‐3T3 cell homogenates.…”
Section: Resultsmentioning
confidence: 99%
“…GA has been shownt oh ave inhibitory activity (87 %a t1m m) when assessed using recombinantG GCT. [18] Therefore, we evaluated the inhibitory effect of GA on GGCT activity in GGCT-NIH-3T3c ell homogenates. GA successfully suppressed GGCT activity in the GGCT-NIH-3T3 cell homogenates nearly to the levels of the control NIH-3T3 cell homogenates (Figure 2A).…”
Section: Ga Is An Effective Ggct Inhibitor In Cell Homogenates But Nomentioning
confidence: 99%
“…H-b 3 -AspA C H T U N G T R E N N U N G (t-Bu)-OH was prepared starting from dimethyl 3-oxoglutarate by a route previously reported by Crossley. [14] Protection of the amino group was accomplished under Schotten-Baumann conditions using Fmoc-Cl to yield the protected derivative Fmoc-b 3 -AspA C H T U N G T R E N N U N G (t-Bu)-OH 8 which was used directly in the solid phase synthesis.…”
Section: Synthesis Of Peptides 2-7mentioning
confidence: 99%
“…Synthesis of blastidic acid : Retrosynthetic analysis of blastidic acid ( 2 ) revealed that this β‐amino acid possesses a hidden symmetry. Therefore, the synthesis began with the preparation of chiral carboxylic acid 35 by enantioselective hydrolysis of meso ‐diester 34 32 using pig liver esterase33 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%